Pengenalan PhET Simulation: Pendorong Eksplorasi Mendalam dan Motivasi Belajar Fisika di SMAN 4 Mataram - Muliadi, Irman; Gunawan, Gunawan; Hudaini, Lalu; Gifari, Putri (Indonesian Journal of Education and Community Services, 2025)
The limited facilities and access to real laboratories constitute a crucial problem in physics learning, hindering in-depth material exploration. This study aims to introduce and integrate PhET Simulation, an interactive virtual laboratory, as an alternative learning media. The method used was an introduction integrated with classroom learning activities in class, through stages of preparation, implementation using PhET Simulation-integrated e-LKPD, and observational evaluation. The results showed the activity ran smoothly, received positive responses, and sparked high enthusiasm from the students. Students actively discussed, explored various features and initiated attempts at experimental variations. PhET Simulation proved to be highly beneficial in increasing learning motivation and encouraging deep exploration, making it an effective and contextual solution when real, practical equipment is unavailable.